Transduction of rat and human adipose-tissue derived mesenchymal stromal cells by adeno-associated viral vector serotype DJ - Ekaterina S. Zubkova (The Company of Biologists, 2021)
Ex vivo, gene therapy is a powerful approach holding great promises for the treatment of both genetic and acquired diseases. Adeno-associated virus (AAV) vectors are a safe and efficient delivery system for modification of mesenchymal stem cells (MSC) that could maximize their therapeutic benefits. Assessment of MSC viability and functional activity after infection with new AAV serotypes is necessary, due to AAV tropism to specific cell types. We infected human and rat adipose-tissue MSC with hybrid AAV-DJ serotype vectors carrying GFP and SCF genes. GFP expression from AAV-DJ was about 1.5-fold superior to that observed with AAV-2 and lasted for at least 21 days as was evaluated by flow cytometry and fluorescence microscopy. AAV-DJ proves to be suitable for the infection of rat and human MSC with a similar efficiency. Infected MSC were still viable but showed a 25-30% growth-rate slowdown. Moreover, we found an increase of SERPINB2 mRNA expression in human MSC while expression of other oxidative stress markers and extracellular matrix proteins was not affected. These results suggest that there is a differential cellular response in MSC infected with AAV viral vectors, which should be taken into account as it can affect the expected outcome for the therapeutic application.